THE EFFECT OF THE NUMBER OF INTERVALS TO THE SENSITIVITY AT ANALYSIS OF DIFFERENTIAL ITEM FUNCTIONING USING MANTEL-HAENSZEL’S CHI-SQUARE PROCEDURE - Heri Retnawati; Kana Hidayati (Program Studi Statistika Unisba, 2004)
At analysis of item bayes or called with differential item functioning (DIF) using the Mantel-Haenszel’s Chi–squareprocedure, the students in a group is grouped pursuant to their reached score, in a certain interval. This research is aimed atrevealing the effect of the number of interval to the sensitivitas at DIF analysis using the Mantel-Haenszel’s Chi-Squareprocedure. Data used at this research is the responses of students of the third grade of SLTPN in Yogyakarta to UAN in2002 / 2003 academic year. Analysis DIFin this research is conducted by making 3, 4, 5, 6, 7, 8, and 9 intervals in students’group pursuant to their reached score using Mantel-Haenszel‘s Chi-Square procedure. The result of this research showedthat the number of intervals causes the differencies of the number of items load DIF significantly in every interval, and itcauses the differencies of sensitivity in the DIF detection; and making 4 intervals in group of students is the most sensitiveway in the DIF detection using Mantel-Haenszel methods, than others.